2022
DOI: 10.3390/jcm11216411
|View full text |Cite
|
Sign up to set email alerts
|

Liparthroplasty for Thumb Carpometacarpal Joint Osteoarthritis: A Case Series with Median 5 Years of Follow-Up

Abstract: Liparthroplasty has recently been discussed as a promising bridging therapy after failed conservative treatment options to postpone arthroplasty surgery of the thumb carpometacarpal joint as long as possible. The current study investigates the sustainability of this method in seven stage II and twenty-four stage III osteoarthritis patients (twenty-seven female and four male cases). Data were evaluated preinterventionally, six months postinterventionally, and two years postinterventionally, as well as a final f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In 2022, the same group published the 5-year results of thumb Liparthroplasty and showed a significant reduction in all post-intervention Disabilities of the Arm, Shoulder and Hand (DASH) scores and pain levels compared with those prior to Liparthroplasty. 35 These data confirm Liparthroplasty as a reliable bridging therapy for preserving joint integrity as long as possible.…”
Section: Discussionsupporting
confidence: 63%
“…In 2022, the same group published the 5-year results of thumb Liparthroplasty and showed a significant reduction in all post-intervention Disabilities of the Arm, Shoulder and Hand (DASH) scores and pain levels compared with those prior to Liparthroplasty. 35 These data confirm Liparthroplasty as a reliable bridging therapy for preserving joint integrity as long as possible.…”
Section: Discussionsupporting
confidence: 63%
“…These study findings highlight the need for comprehensive interventions that address both medication management adherence and the factors contributing to reduced quality of health status among individuals with osteoporosis. The development of educational programs, follow-up strategies, and alternative dosing regimens may contribute to more effective management and enhanced quality of life for this patient population [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Froschauer at et al were the first authors describing the technique of liparthroplasty in a series of patients with carpo-metacarpal arthritis [27]. In a recently published case series, the same author reported significant improved disabilities of function of the arm, shoulder, and hand (DASH) score after a median five-years follow-up [29]. Jo et al reported encouraging results after intra-articular injection of adipose-derived mesenchymal stem cells for the treatment of osteo-arthritis of the knee [30].…”
Section: Discussionmentioning
confidence: 99%